Customer Data Analytics- Revolutionizing Marketing and Customer Retention in Retail and e-commerce - Shetty, Spurti Manjunath (2016)
The main aim of the study is to understand customer data analytics and its applications in marketing in retail and e-commerce sector. Retail and e-commerce companies have millions of customers. With completion everywhere and with the introduction of loyalty cards and discounts it has become extremely difficult to retain customers and manage them. The paper researches about the way companies have managed to retain customers and attracted new ones using customer data analytics and the various models for customer data analytics, data mining techniques and predictive analysis to run algorithms in order to get output in the form of information that can be used to make critical decisions. The study on the advantage card campaign boots shows how boots used the vast customer database to communicate with customers, engage them and retain them against all odds and challenges. It constantly updated its algorithms, analytical models and the way it targeted customers to succeed in what could be called one of the most popular advantage card story. The paper also discusses about the limitations of customer data analytics and recommendations to improve.